Haplotype of multiple polymorphisms resolved by enzymatic amplification of single DNA molecules. - Ruano, G (1990)
We have developed a reliable method for the direct resolution of haplotypes or linkage phase from individuals who are multiply heterozygous in a given genomic region. The method is based on single-molecule dilution (SMD) of genomic template and amplification via biphasic polymerase chain reaction (booster PCR). We have verified the feasibility of the SMD method for a highly polymorphic region within the beta-globin cluster by analysis of triply heterozygous individuals of known haplotype. This approach should be useful in many studies in population or evolutionary genetics and in a variety of clinical settings.